Incidental Finding of Posterior Fossa Epidermoid, In a Head Trauma Patient: A Case Report - Baskota, Narendra Prasad; Singh, K. (Journal of Nepalgunj Medical College, 2019)
Incidental findings of brain lesions in head injury are seen frequently. In our region NCC is common, but in literature meningioma andarachnoid cyst are common. Here we report a case of incidental finding of posterior fossa epidermoid in a 25 years old male patient who had history of minor head trauma which was operated with relatively uneventful post operative period.